SELECTION AND THE DEVELOPMENT OF THE HUMAN RESOURCES OF THE SA DEFENCE FORCE FOR THE YEAR 2000 - Eberlein, R. (Scientia Militaria - South African Journal of Military Studies, 2012)
In a series of articles (Eberlein, 1989; 1990; and 1991) an attempt has been made to describe the need for an integrated approach to human resources development in the SA Defence Force (SADF); the role of educational technology in that development; and the need for the professional development of trainers in South Africa. For the convenience of the reader who has neither the time nor the endurance to study those articles, the contents will be repeated synoptically here, with the necessary emphasis on the subject of this paper. Such repetition is not merely self-indulgence on the part of the author, but an essential element of the framework into which personnel selection fits.